The Application of Publicly Engaged Scholarship to Graduate Education - Jed Metzger (Journal of Community Engagement and Scholarship, 2022)
Review of the book: Amanda Gilvin, Georgia M. Roberts, and Craig Martin (Eds.), Collaborative Futures: Critical Reflections on Publicly Active Graduate Education. Syracuse, NY: The Graduate School Press., 2012, 409 pages. ISBN: 978-0-9777847-5-2